On the Dynamic Interaction of n-Butane with Imidazolium-Based Ionic Liquids - Bhuin, Radha Gobinda; Winter, Leonhard; Lexow, Matthias; Maier, Florian; Steinrück, Hans-Peter (Angewandte Chemie International Edition, 2020)
The impact of a reactant from the gas phase on the surface of a liquid and its transfer through this gas/liquid interface are crucial for various concepts applying ionic liquids (ILs) in catalysis. We investigated the first step of the adsorption dynamics of n-butane on a series of 1-alkyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ILs ([CnC1Im][Tf2N]; n=1, 2, 3, 8). Using a supersonic molecular beam in ultra-high vacuum, the trapping of n-butane on the frozen ILs was determined as a function of surface temperature, between 90 and 125 K. On the C8- and C3-ILs, n-butane adsorbs at 90 K with an initial trapping probability of ≈0.89. The adsorption energy increases with increasing length of the IL alkyl chain, whereas the ionic headgroups seem to interact only weakly with n-butane. The absence of adsorption on the C1- and C2-ILs is attributed to a too short residence time on the IL surface to form nuclei for condensation even at 90 K.
CRIS-Team Scopus Importer:2020-07-10
Keywords: gas-surface dynamics; ionic liquids; molecular beam; n-butane; trapping and adsorption